Understanding beneficiary satisfaction through logistics efficiency and digital technology in Indonesia's free nutritious meal program - Vinanda Vinanda; Tien Yustini (Institute of Computer Science (IOCS), 2026)
High malnutrition rates among pregnant women, infants, and children pose a significant challenge to Indonesia's human resource development and the